Nursing workload in an inpatient unit (Revista Latino-Americana de Enfermagem, 2011)
This study evaluated the nursing workload in an inpatient unit of a university hospital. This descriptive study applied the Nursing Activities Score (NAS) over the course of 30 consecutive days. A total of 1,080 observations were obtained from the medical files of 156 patients. The average scored obtained in the NAS instrument was 47.31%. Considering that each single NAS score corresponds to 0.24 hours, an average of 11.35 hours of nursing care was required. This amount of hours correspond to the profile of inpatients demanding semi-intensive and intensive care, suggesting that the NAS can be used to evaluate the workload of the nursing staff in this unit.